A Review of Pleiotropic Potential of Erythropoietin as an Adjunctive Therapy for COVID-19 - Fatemeh EmamiPari; Soroush Kamali; Ghazaleh Nikzad; Narges Roosta Navi; Sanaz Soltani; Mohamad Reza Kalani (Golestan University Of Medical Sciences, 2022)
Coronavirus disease 2019 (COVID-19) is a severe acute respiratory disease with a high prevalence. According to the research and statistical data, in January 2021, there have been 92,262,621 confirmed cases of COVID-19 and more than two million deaths. Infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the main cause of this disease. In addition to the respiratory system, the disease affects the gastrointestinal tract, central-peripheral nervous system, circulatory system, and kidneys. Therefore, any therapeutic action to reduce COVID-19-related symptoms and complications is essential. In this study, we conducted a systematic review of the published literature and preprints on the efficacy of erythropoietin (EPO) and recombinant human EPO as a safe stimulant and tissue protector in the treatment of COVID-19. We also briefly described the structure of coronavirus, its pathogenesis, and the structure of EPO and recombinant human EPO. All relevant articles published in the Science Direct, PubMed, and Google Scholar databases were searched.  According to the results, EPO is a cytoprotective cytokine induced by hypoxia. The pleiotropic effects of EPO are associated with its erythrocyte-forming, anti-apoptotic, anti-inflammatory activities. It also exerts protective effects on the heart, lungs, kidneys, arteries, and central and peripheral nervous systems. It has been demonstrated that EPO can increase hemoglobin levels, thereby increasing oxygen delivery to the tissues. Therefore, recombinant human EPO therapy can be used for counteracting the adverse effects of COVID-19 including hypoxic myocarditis, acute renal failure, pulmonary edema, and brain-spinal cord ischemic injury. Overall, the use of EPO and recombinant human EPO therapy increases blood coagulation, tumor growth, thromboembolism, and purification of red blood cells, which must be accompanied by anticoagulants such as heparin.